2018
DOI: 10.1101/317073
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathways to Consumers’ Minds: Using Machine Learning and Multiple EEG Metrics to Increase Preference Prediction Above and Beyond Traditional Measurements

Abstract: A basic aim of marketing research is to predict consumers' preferences and the success of marketing campaigns in the general population. However, traditional behavioral measurements have various limitations, calling for novel measurements to improve predictive power. In this study, we use neural signals measured with electroencephalography (EEG) in order to overcome these limitations. We record the EEG signals of subjects, as they watched commercials of six food products. We introduce a novel approach in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 63 publications
(91 reference statements)
1
18
0
Order By: Relevance
“…It has been previously shown that prediction accuracy is far better for products that are distant in their preferences, while prediction accuracy is at chance level for products which subjects are indifferent to (Hakim et al, ; Levy et al, ; Telpaz et al, ). Another study has shown that it is harder to discriminate between the neural activation of similar brands (Chen, Nelson, & Hsu, ).…”
Section: Prospects and Challenges For The Futurementioning
confidence: 99%
“…It has been previously shown that prediction accuracy is far better for products that are distant in their preferences, while prediction accuracy is at chance level for products which subjects are indifferent to (Hakim et al, ; Levy et al, ; Telpaz et al, ). Another study has shown that it is harder to discriminate between the neural activation of similar brands (Chen, Nelson, & Hsu, ).…”
Section: Prospects and Challenges For The Futurementioning
confidence: 99%
“…We classified these predictive features based on the EEG signal types: (1) rhythms; and (2) transient activities. [17] Viewing brands and products ERP P300 BCI [11] Watching TV ads EEG Alpha (for emotional state) EMG, BCI and GSR [36] Viewing brands and images ERP N200 and P300 BCI [37] Watching TV ads EEG Alpha band frontal asymmetry BCI [35] Watching TV ads EEG Theta and gamma Heart rate, BCI and GSR [28] Watching TV ads EEG Asymmetrical increase in theta and alpha in PSD BCI [38] Viewing brand names ERP N400 BCI and EOG for eye movement [18] Viewing products and prices ERP FN400, LPC, and P200 BCI [39] Viewing products EEG Alpha, beta, theta, gamma, and delta BCI, Eye tracking [40] Viewing products ERP P300 BCI [41] Watching TV ads EEG Theta and alpha Heart rate, BCI and GSR [3] Viewing products ERSP and ERP Theta, N200, and FRN BCI [24] Watching ads (movie trailers) EEG (64 electrodes) Beta and gamma oscillations BCI and EOG for eye movement (2 electrode) [20] Watching TV ads dense-array EEG Three epochs: 200-350, 350-500, and 500-800 BCI [42] Viewing brand names ERP LPP BCI [43] Viewing product images ERP N200, LPP, and PSW BCI [30] Watching ad videos EEG Theta and alpha Heart rate, BCI and GSR [22] Viewing product images EEG Delta, theta, alpha, beta, and gamma BCI [29] Viewing product images EEG Alpha BCI [44] Viewing ads of food products EEG Delta, theta, alpha, beta, and gamma BCI [32] Viewing products and prices EEG Theta BCI [31] Tasting drinks EEG Alpha BCI [33] Viewing and touching products EEG Alpha and theta BCI [27] Viewing product images ERSP, ERP Theta, beta and N200 BCI [45] Viewing tourism images, videos and words EEG Delta, theta, alpha, beta and gamma BCI and GSR…”
Section: Predictive Features For the Preferencesmentioning
confidence: 99%
“…Low-pass filter 3 [22,24,38] Band-pass filters 10 [3,11,15,20,28,[39][40][41]44,53] Down sampling 3 [11,15,44] Average 7 [3,15,27,37,38,40,54]…”
Section: Number Of Studies References Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations